Hubungan Pengetahuan Dengan Sikap Ibu Hamil Trimester III Tentang Inisiasi Menyusui Dini Di Wilayah Kerja Puskesmas Megang Kota Lubuklinggau Tahun 2025 - Yanti Kasumah; Tuti Rohani; Murwati Murwati (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The IMD coverage in South Sumatra in 2023 is 88.6%, down from 94.8% in 2022. The highest coverage was in East OKU Regency at 98.3%. Meanwhile, the coverage success rate in Lubuk Linggau City was 64.5% with a target success rate of close to or more than 80%, which refers to the national exclusive breastfeeding target of increasing exclusive breastfeeding coverage to at least 80% (South Sumatra Health Office 2023). The purpose of this study was to determine the relationship between knowledge and the attitudes of pregnant women in their third trimester regarding early breastfeeding initiation in the Megang Community Health Centre Working Area, Lubuklinggau City, in 2025.The research method used was descriptive quantitative research with a cross-sectional approach. The sampling technique used was total sampling with a sample size of 32 people.The results of the univariate analysis showed that a small proportion of respondents (21.9%) had insufficient knowledge and almost half of the respondents (31.3%) had unsupportive attitudes. The results of the bivariate analysis of knowledge and attitudes of third trimester pregnant women regarding early breastfeeding initiation (0.003) showed that there is a relationship between knowledge and attitudes of third trimester pregnant women regarding early breastfeeding initiation in the Megang Community Health Centre Working Area, Lubuklinggau City, in 2025. Pregnant women in their third trimester who participated in the study are expected to utilise the information obtained through this research to increase their knowledge, improve their attitudes, and prepare themselves to implement EBI after delivery.